تأثير برنامج تدريبي في تطوير مستوى القدرات البدنية وتخفيض وزن الجسم لبعض التدريسيين في كلية التربية الاساسية - شاكر, نبيل محمود; وهيب, ياسر محمود (Sulaimani Journal for Humanities, 2018)
The researchers identify the study the problem, which include weakness of some of the physical attributes and obesity for some Tdrisie basic / Diyala University Education College, where he was chosen (18) teaching at random, was applied training modules for three months by two units training every week, to develop some of the physical attributes and reduce weight, and that came with good results led to achieving the goals of the study.